Diphenylphosphine oxide-based host materials for green phosphorescent organic light-emitting devices. (November 2017) - Yang, Tingting; Xu, Huixia; Xi, Zhaoyang; Wang, Kexiang; Tao, Peng; Sun, Peng; Zhao, Bo; Miao, Yanqin; Lian, Hong; Wang, Hua; Xu, Bingshe; Wong, Wai-Yeung
Abstract: Two novel host materials based on the diphenylphosphine oxide (DPPO) and spirofluorene were designed and facilely synthesized by tuning the ratio of donor spirofluorene units and acceptor DPPO units from 1: 1 to 1: 2, i. e., (4-(9, 9′-spirobi[fluoren]-2-yl)phenyl)diphenylphosphine oxide (SPDPPO) and (9, 9′-spirobi[fluorene]-2, 7-diylbis(4, 1-phenylene))bis(diphenylphosphine oxide) (SBPBDPPO). Furthermore, 3, 6-disubstituted spirofluorene possesses better thermal stability performance, for instance, higher glass transition temperatures (SPDPPO of 140 °C and SBPBDPPO of 172 °C). The phosphorescent organic light-emitting devices (PhOLEDs) were fabricated by doping tris(2-phenylpyridine)iridium (Ir(ppy)3 ) in hosts as light-emitting layer. The PhOLEDs employed SPDPPO as host exhibited a low turn-on voltage of 3.0 V and the maximum current efficiency of 36.5 cd/A, power efficiency of 32.8 lm/W and a maximum external quantum efficiency ( EQE ) of 10.5%, respectively. Graphical abstract: The two host materials (SPDPPO and SBPBDPPO) were designed and synthesized. The green PhOLEDs using Ir(ppy)3 as phosphorescent dopants were fabricated and hosted by SPDPPO display performances with η cmax of 36.5 cd/A and low efficiency roll-off. Highlights: Two host materials (SPDPPO and SBPBDPPO) were designed and synthesized by using diphenylphosphine oxide as acceptor and spirobifluorene units as donor. They exhibited excellent thermal properties with the T g of SPDPPO and SBPBDPPO of 140 and 172 °C. The green PhOLEDs hosted by SPDPPO using Ir(ppy)3 as dopant displays better performances with η cmax of 36.5 cd/A.